The Utilization of Digital Marketing and Financial Administration Management to Improve Business Performance in Podomoro Tip Top Stores - Lestari, Lyssia Putri; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2023)
The development of the retail business today is growing rapidly, one of which is the business of providing daily consumer goods. This condition encourages high business competition, thereby requiring business actors to be able to excel in the competition. This community service program aims to help improve retail business performance at Tip Top Podomoro Shop. The programs implemented include: education on the use of social media as an online marketing tool, creating online promotional content, using Shopee e-commerce as a sales medium, providing an online payment system with QRIS, and improving financial management.